Confidence interval for survival model based on partly interval-censored data - Zainudin, Norazelah; Elfaki, Faiz Ahmed Mohamed; Yeakub Ali , Mohammad (2015)
Cox Proportional Hazard model and its application on Empirical Likelihood (EL) based on Partly Interval-Censored data is proposed in this paper. Also, this paper will provide the information on the new version of Empirical Likelihood namely Adjusted Empirical Likelihood (AEL) that serve the purpose of improvising EL to solve the EL under coverage problem. A major advantage of the approach is its simplicity and it can be easily implemented by using R software. Simulation studies are conducted which indicate that the approach performs well comparable to the existing methods